Farm sector performance and reform agenda - Landes, Rip; Gulati, Ashok (2004)
Recent political changes in India have brought back agriculture to the centre stage of policy discussions. How long it stays there is yet to be seen. But it would be worth analysing the structural and policy-induced changes in agriculture since the reforms started in 1991, and try to build a political concensus on the reform agenda that can put agriculture on a higher growth trajectory, makes it globally competitive and enables the masses to share in its gains, and is also sustainable in the long run. This paper is an attempt in that direction. - Reproduced.
Keywords: Agricultural planning